SOSIALISASI TRANSAKSI SYARIAH DAN KOPERASI SYARIAH - Siti Fatimah Rofi; Purnama Putra; Mas Deden Tirtajaya (LPPM Universitas Islam 45, 2022)
One of the objectives of the establishment of Islamic financial institutions is to introduce sharia principles in the economic world. Officially, the Indonesian government has supported the existence of Islamic financial institutions in Indonesia by issuing a law as its official form. Sharia Financial Services Cooperative is a microfinance institution that provides sharia financial transaction services. Transactions in Sharia Cooperatives are based on Islamic jurisprudence so they are not widely known by people in general. Therefore, this Community Service aims to introduce the types of transactions that exist in Sharia Cooperatives so that people can choose the type of contract that suits their financial transaction needs. The method used in this Community Service is in the form of counseling or outreach to the Kaliabang village community with the results of the socialization of sharia transactions and sharia cooperatives showing an increase in the knowledge and understanding of citizens about contracts in Islamic sharia transactions and any sharia cooperative products based on these contracts.